PERAN KREATIVITAS DAN INOVASI PELAKU USAHA DALAM DIVERSIFIKASI PRODUK KULINER PADA KEDAI STEAK & CHICKEN DI KAB. MAGETAN TAHUN 2014 (IMPLEMENTASI PENDIDIKAN KEWIRAUSAHAAN) - Sarijani, Endang; M.Si, Baedhowi; Sawiji, Hery (Jurnal Pendidikan Insan Mandiri, 2016)
The objectives of this research are to investigate: (1) the role of creativity of the owner of Steak & Chicken Stall in menu type selection, business identity selection, business site selection, each menu?s taste creation, and menu labeling idea in the culinary product diversification; (2) the innovation of the owner of Steak & Chicken Stall in the offered products, business facilities, promotion of products, products which are not preferred by consumers in the culinary product diversification; and (3) the role of creativity and innovation in the culinary product diversification, which is done by the owner of Steak & Chicken Stall.            This research used the descriptive research method. The samples of research were taken by using the accidental sampling technique for the consumers and purposive sampling for the owner and employees of the stall, Head of the Office of Industry and Trade of Magetan Regency. The data of research were gathered through in-depth interview, observation, and documentation. They were analyzed by using the interactive model of analysis.            The result of research shows that creativity and innovation are very much required for product diversification, as they can create new ideas for culinary products.  This in turn will increase the sale turnover and income. Product diversification is truly needed if the business condition begins to be threatened by new competitors or to be left by customers. To fix it, a self-exploration attitude is required, that is, the ability to sharpen creativities and implement them in real actions as an embodiment of innovations, so as to have extraordinary contributions to the increase of sale turnovers, customers, and profits.Keywords: Creativity, innovation, entrepreneurship, and product diversification